Nano Learning Strategies in Enhancing Students Vocabulary - Azwati, Ilham Ma’arij; Munir, Munir; Muliati, Andi (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The purpose of this study was to determine the efficiency of nano learning methodologies with the Tiktok application in enhancing students' vocabulary. The study used a quantitative approach using an experimental design that was quasi-experimental. The population of this study was students in class VIII at SMPN 4 Sungguminasa, and The total population here is 330 students from eight grade while the sample population is 60 students. The data were collected through pre-test and post-test. The results of the data analysis show that the mean score of post-test significantly higher than the pre- test, where the category was improved from very poor (37) to a good (73) category. The data was analyzed used the Wilcoxon test which shows Asymp. Sig. (2-tailed) namely 0.022 and 0.135 bigger than 0.005 (<0.005) indicating that the alternative hypothesis is accepted and in the Mann Whitney U test Asymp. Sig. (2-tailed), namely 0.135, bigger than 0.005 (0.135<0.005) indicating that there is a significant difference so it can be concluded that the the use of nano learning strategies has influenced the students' vocabulary enhancement positively, it is shown that there are differences in the average between the learning outcomes of the pretest and the posttest, therefore H0 is rejected and H1 is accepted. Based on the hypothesis of this study, there is a significant difference between the control and experimental groups when using nano learning strategies to enhance vocabulary skills.Keywords: Nano learning, vocabularies, tiktok application.